2011
DOI: 10.33549/physiolres.931952
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Plasma Obestatin, Ghrelin and NPY in Anorexia and Bulimia Nervosa Patients Before and After a High-Carbohydrate Breakfast

Abstract: Peptides ghrelin, obestatin and neuropeptide Y (NPY) play an important role in regulation of energy homeostasis, the imbalance of which is associated with eating disorders anorexia (AN) and bulimia nervosa (BN). The changes in ghrelin, obestatin and NPY plasma levels were investigated in AN and BN patients after administration of a high-carbohydrate breakfast (1604 kJ). Eight AN women (aged 25.4±1.9; BMI: 15.8±0.5), thirteen BN women (aged 22.0±1.05; BMI: 20.1±0.41) and eleven healthy women (aged 25.1±1.16; BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 35 publications
2
18
0
3
Order By: Relevance
“…Although, in general, the size of postprandial changes in ghrelin in the present study is comparable to previous studies, we also found that women with a history of AN showed higher unstimulated (fasting) and stimulated (postprandial) ghrelin levels compared to women without a history of AN. Our finding appears to stand in contrast to prior research in remitted patients with AN, which has shown that ghrelin tends to decrease from elevated to normal concentrations as weight is being restored .…”
Section: Discussionsupporting
confidence: 89%
“…Although, in general, the size of postprandial changes in ghrelin in the present study is comparable to previous studies, we also found that women with a history of AN showed higher unstimulated (fasting) and stimulated (postprandial) ghrelin levels compared to women without a history of AN. Our finding appears to stand in contrast to prior research in remitted patients with AN, which has shown that ghrelin tends to decrease from elevated to normal concentrations as weight is being restored .…”
Section: Discussionsupporting
confidence: 89%
“…Fasting plasma NPY has previously been investigated in AN patients and the data are controversial. Indeed, some authors report decreased levels of plasma NPY in AN patients [ 8 ], or increased concentrations [ 9 – 12 ], or unchanged levels [ 13 ]. In our study, we found higher NPY levels in AN only 0900h (in the postprandial period) but not in fasting conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these data, obestatin levels increased with body weight reduction following gastric banding and sleeve gastrectomy surgery in obese and T2DM patients, respectively, and with standard weight loss in obese children (Haider et al ., ; Arrigo et al ., ; Lee et al ., ). Obestatin levels were also higher in individuals with anorexia nervosa (Harada et al ., ; Monteleone et al ., ; Germain et al ., ; Sedlácková et al ., ; Uehara et al ., ; Sedlackova et al ., ; Shen et al ., ), and whilst they were decreased with hypothyroidism (associated with weight gain), they were increased with hyperthyroidism (associated with weight loss) (Emami et al ., ). Interestingly, the combination of preproghrelin polymorphisms Leu 72 Met and Gln 90 Leu have been associated with increased risk of anorexia nervosa (Dardennes et al ., ).…”
Section: Metabolic Actions Of Obestatinmentioning
confidence: 98%
“…Although the majority of studies appear to support an inverse relationship between circulating obestatin and obesity/diabetes, increased obestatin levels have also been reported in patients with obesity, metabolic syndrome, impaired glucose control, T1DM, Prader–Willi syndrome (which is linked with obesity) and bulimia nervosa (Butler and Bittel, ; Vicennati et al ., ; Reinehr et al ., ; Sedlácková et al ., ; Arrigo et al ., ; Sedlackova et al ., ; Mora et al ., ; Prodam et al ., ; Wali et al ., ), whilst levels have been shown to be decreased in hyperthyroidism and in pregnant women 24 h post‐partum (which typically increases insulin sensitivity) (Baykus et al ., ; Gurgul et al ., ). Other studies have found obestatin levels to be unaltered following gastric surgery‐induced weight loss in both obese and T2DM patients (Roth et al ., ; Lee et al ., ; Siejka et al ., ) and in bulimia nervosa (Monteleone et al ., ).…”
Section: Metabolic Actions Of Obestatinmentioning
confidence: 99%